Heat-Labile Enterotoxin IIa, a Platform To Deliver Heterologous Proteins into Neurons - Chen Chen (American Society for Microbiology, 2015)
ABSTRACT Cholera toxin (CT) and the related heat-labile enterotoxins (LT) of Escherichia coli have been implicated as adjuvants in human therapies, but reactivity upon intranasal delivery dampened efforts to develop other clinical applications. However, each CT family member variant has unique biological properties that may warrant development as therapeutic platforms. In the current study, a nontoxic variant of the heat-labile enterotoxin IIa (LTIIa) was engineered to deliver heterologous, functional proteins into the cytosol of neurons. As proof of principle, the LTIIa variant delivered two cargos into neurons. LTIIa delivered β-lactamase efficiently into cells containing complex gangliosides, such as GD1b, as host receptors. LTIIa delivery of β-lactamase was sensitive to brefeldin A, an inhibitor that collapses the Golgi compartment into the endoplasmic reticulum, but not sensitive to treatment with botulinum neurotoxin D (BoNT/D), an inhibitor of synaptic vesicle cycling. LTIIa delivered a single-chain, anti-BoNT/A camelid antibody that inhibited SNAP25 cleavage during post-BoNT/A exposure of neurons. Delivery of functional, heterologous protein cargos into neurons demonstrates the potential of LTII variants as platforms to deliver therapies to inactivate toxins and microbial infections and to reverse the pathology of human neurodegenerative diseases.IMPORTANCE This study engineered a protein platform to deliver functional, heterologous proteins into neurons. The protein platform developed was a variant of the heat-labile enterotoxin IIa (LTIIa) which lacked the catalytic domain, yielding a nontoxic protein. As proof of principle, LTIIa variants delivered two functional proteins into neurons, β-lactamase and a camelid antibody. These studies show the utility of LTIIa variants to deliver therapies into neurons, which could be extended to inactivate toxins and microbial infections and potentially to reverse the progression of neurological diseases, such as Alzheimer's disease and Parkinson's disease.